Multicenter study evaluating extraprostatic uptake of 11C-choline, 18F-methylcholine, and 18F-ethylcholine in male patients: physiological distribution, statistical differences, imaging pearls, and normal variants. Issue 11 (November 2015) - Haroon, Athar; Zanoni, Lucia; Celli, Monica; Zakavi, Rasoul; Beheshti, Mohsen; Langsteger, Werner; Fanti, Stefano; Emberton, Mark; Bomanji, Jamshed
Abstract : Aim: The aim of the study was to evaluate the visceral localization of the three most commonly used choline-based radiotracers ( 11 C-choline, 18 F-methylcholine, and 18 F-ethylcholine) with the aim of analyzing uptake in metabolically and anatomically disease-free patients. Materials and methods: A total of 1250 standardized uptake values (SUVmax, SUVmean ) were analyzed in 45 anatomical regions in 45 patients (15 patients with 11 C-choline, 15 with 18 F-methylcholine, and 15 with 18 F-ethylcholine). These patients were selected from a cohort of 3721 choline PET/computed tomography studies performed at three teaching hospitals over a period of 10 years. They had no evidence of metabolically active primary disease, metastatic disease, or altered morphology on the computed tomography component of the study or any evidence of disease elsewhere on other imaging modalities. The sites of primary disease (prostate and seminal vesicles) were excluded from evaluation. Results: No adverse effect was documented when using the three tracers. Visceral localization was the same for all three tracers. Viscera with a statistical difference in intensity of uptake included the choroid plexus ( P =0.0001), occipital lobe ( P =0.014), parietal lobe ( P =0.008), cerebellum ( P =0.003), parotid gland ( P =0.005), submandibular gland ( P =0.001), tonsils ( P =0.001), thyroid ( P =0.0001), lungs ( P =0.001), aorta ( P =0.001), pulmonary artery ( P =0.0001), liver segments I ( P =0.005), III ( P =0.005), IVB ( P =0.03), and V ( P =0.01), spleen [hilum ( P =0.0009), body ( P =0.0001)], pancreas [head ( P =0.0001), body ( P =0.01), tail ( P =0.002)], esophagus ( P =0.001), stomach ( P =0.0001), duodenum ( P =0.0002), large intestine ( P =0.008), and rectum ( P =0.0001). Elsewhere, no statistical difference was observed. Excreted activity was noted in the kidneys and bladder. Conclusion: This study demonstrates that the visceral localization of 11 C-choline, 18 F-methylcholine, and 18 F-ethylcholine in disease-free patients is similar. Depending on the tracer uptake pattern, the viscera can be divided into two distinct categories: those with a statistically significant difference in uptake and those with no difference in uptake. The study outlines the range of SUVs for various organs for the three tracers and identifies some of the potential pitfalls in the evaluation of 'nonavid' but clinically significant presentation of different disease entities.